Developing strategies for integrated management of Phytophthora root rot and gummosis in kinnow mandarin (Citrus reticulata) - AKHILESH KUMAR SRIVASTAVA, PARDEEP KUMAR, ROOP SINGH MEENA, CHANDERBHAN; RAMSWROOP KOLI, SHRI KISHAN BAIRWA (Indian Phytopathology, 2015)
A field experiment was conducted during 2011-12 to 2013-14 for integrated management of Phytophthora root rot and gummosis on Kinnow mandarin (Citrus reticulate Blanco). Among various treatments tried, bioagents based treatment of stem painting with Bordeaux paste (copper sulphate, lime and water in a 3:3:30 ratio), followed by application of Trichoderma viride (2 × 107 cfu/gm) at 100g + Pseudomonas fluorescens (2 × 108 cfu/gm) at 100g/ tree with carrier material FYM proved most effective which significantly (P=0.05) recovered lesion size (22.82%) and reduced feeder root rot index (24.39%). Minimum fruit dropping (20.74%) and maximum fruit yield in terms of number of fruits (1084 fruits/tree) as well as fruit yield (212.84 kg/tree) were also recorded in this treatment and was significantly (P=0.05) superior to the control. The treatment module of stem painting with Bordeaux paste followed by application of T. harzianum (2 × 107cfu/g) at 100g/tree + P. fluorescens (2 × 108 cfu/g) at 100g/tree without carrier material was also found effective and next in order to manage this disease. The reduction in gummosis symptoms were observed mild to moderate in all treatments compared to the control where severe gummosis occurred.